Portfolios to Reflect on Teaching Practices (2020)
ABSTRACT: This paper was aimed to determine the effectiveness of portfolios to reflect on teaching practices with preservice teachers at Escuela Normal Superior de Medellín where students have been provided with tools and didactic elements to develop their professions with children. Data were collected by means of interviews, journal reports and students’ reflections. Results showed that the portfolio is a potential tool for teaching learning practices because it allows students to monitor their learning processes, self-assess, improve their performance and reflect on their future practices. Moreover, the portfolio development fosters preservice teachers’ professional development, and the ICT's and virtual environments play an important role in its construction.